A new fiscal policy for Germany - Philippa Sigl-Gloeckner; Max Krahé; Pola Schneemelcher; Florian Schuster; Viola Hilbert; Henrika Meyer (Forum for a New Economy, 2021)
The sustainability of public finances should be measured by the debt-to-GDP ratio; the debt-to-GDP ratio is best controlled by keeping the deficit in check. For decades, these ideas shaped German fiscal policy. In 2009, with the introduction of the debt brake, this approach found its way into the German constitution. Recent research, however, has shown that this paradigm yields suboptimal results in the current environment: It neither ensures the long-term sustainability of public finances, nor limits external imbalances, nor effectively contributes to solving the challenges Germany faces today, in particular decarbonisation and demographic change. As this is increasingly being recognised, a lively debate on the future of fiscal rules has developed, both in Germany and internationally. This working paper contributes to that debate by developing reform ideas that depart from a positive goal for fiscal policy rather than from the deficiencies of the current rules. The paper starts off with an overview over the current reform debate. Following this literature review, three closely related questions are answered: what is the right objective for fiscal policy? What might an institutional framework look like to put this objective into practice? And what concrete, politically realistic reform options could move us in that direction? In response to the three questions, we identify sustainable full capacity utilisation of the economy as a sound objective for fiscal policy; make a proposal for a framework consisting of four components; and develop detailed proposals for initial re-form steps to begin implementing this framework in Germany, including an adjustment of the cyclical component of the debt brake (governed by ordinary law), introducing an investment fund for municipal investments, and adding a watchman indicator for rising interest costs. – – Ueber Jahrzehnte war die deutsche Fiskalpolitik von der Idee gepraegt, dass die Tragfaehigkeit der oeffentlichen Finanzen an der Schuldenquote zu messen sei; die Schuldenquote wiederum sei am besten ueber das jaehrliche Haushaltsdefizit zu kontrollieren. Mit der Einfuehrung der Schuldenbremse fand dieser Ansatz 2009 Eingang in die deutsche Verfassung. Die neuere Forschung hat jedoch herausgearbeitet, dass dieses Paradigma im heutigen Kontext zu suboptimalen Ergebnissen fuehrt: Insbesondere gewaehrleistet es weder die langfristige Tragfaehigkeit der oeffentlichen Finanzen noch ein aussenwirtschaftliches Gleichgewicht noch einen effizienten Beitrag zur Loesung der heute vor uns stehenden Herausforderungen, insbesondere der Dekarbonisierung und des demographischen Wandels. Eine wachsende Erkenntnis dieser Tatsache hat sowohl in Deutschland als auch international zu einer lebhaften Debatte ueber die Zukunft von Fiskalregeln gefuehrt. Dieses Working Paper baut auf der Debatte auf und geht einen Schritt weiter, indem es nicht von den Unzulaenglichkeiten des heutigen Paradigmas, sondern von einer positiven Zielsetzung aus in Richtung neuer Reformideen denkt. Einfuehrend geben wir einen Ueberblick zum Stand der Diskussion um Alternativen und Reformen der Schuldenbremse. Anschliessend werden drei eng miteinander verknuepfte Fragen beantwortet: was ist die richtige Zielsetzung fuer Fiskalpolitik? Wie koennte ein institutionelles Rahmenwerk aussehen, um diese Zielsetzung in die Praxis umzusetzen? Und welche konkreten, politische realistischen Reformoptionen koennten uns in diese Richtung bewegen? Dabei identifizieren wir nachhaltige Vollauslastung der Wirtschaft als sinnvolles Ziel fuer Fiskalpolitik; machen einen Vorschlag fuer ein viergliedriges Rahmenwerk, und entwickeln detaillierte Vorschlaege fuer erste Reformschritte, mit denen dieses Rahmenwerk in Deutschland umgesetzt werden koennte, darunter eine Anpassung der einfachgesetzlich geregelten Konjunkturkomponente der Schuldenbremse, die Einfuehrung einer Investitionsgesellschaft fuer kommunale Investitionen, sowie die Einfuehrung eines Fruehwarnindikators fuer Zinskosten.
Keywords: E62; E02; H62; H63; 330; Fiscal Policy; Fiscal Rules; Debt Brake; Debt Management